Molecular Characterization of the RNA-Binding Protein Quaking-a in Megalobrama amblycephala: Response to High-Carbohydrate Feeding and Glucose/Insulin/Glucagon Treatment - Shi, Hua-Juan; Liu, Wen-Bin; Xu, Chao; Zhang, Ding-Dong; Wang, Bing-Ke; Zhang, Li; Li, Xiang-Fei (Frontiers in Physiology, 2018)
The RNA-binding protein quaking-a (Qkia) was cloned from the liver of blunt snout bream Megalobrama amblycephala through the rapid amplification of cDNA ends method, with its potential role in glucose metabolism investigated. The full-length cDNA of qkia covered 1,718 bp, with an open reading frame of 1,572bp, which encodes 383 AA. Sequence alignment and phylogenetic analysis revealed a high degree of conservation (97-99%) among most fish and other higher vertebrates. The mRNA of qkia was detected in all examined organs/tissues. Then, the plasma glucose levels and tissue qkia expressions were determined in fish intraperitoneally injected with glucose (1.67 g per kg body weight (BW)), insulin (0.052 mg/kg BW) and glucagon (0.075 mg/kg BW) respectively as well as in fish fed two dietary carbohydrate levels (31% and 41%) for 12 weeks. Glucose administration induced a remarkable increase of plasma glucose with the highest value being recorded at 1 h. Thereafter, it reduced to the basal value. After glucose administration, qkia expressions significantly decreased with the lowest value being recorded at 1 h in liver and muscle and 8 h in brain, respectively. Then they gradually returned to the basal value. The insulin injection induced a significant decrease of plasma glucose with the lowest value being recorded at 1 h, whereas the opposite was true after glucagon load (the highest value was gained at 4 h). Subsequently, glucose levels gradually returned to the basal value. After insulin administration, the qkia expressions significantly decreased with the lowest value being attained at 2 h in brain and muscle and 1 h in liver, respectively. However, glucagon significantly stimulated the expressions of qkia in tissues with the highest value being gained at 6 h. Moreover, high dietary carbohydrate levels remarkably increased plasma glucose levels, but down-regulated the transcriptions of qkia in tissues. These results indicated that the qkia gene of blunt snout bream shared a high similarity with that of the other vertebrates. Glucose and insulin administration, as well as high-carbohydrate feeding, remarkably down-regulated its transcriptions in brain, muscle and liver, whereas the opposite was true after the glucagon load.